Cadmium-Tolerant and -Sensitive Cultivars Identified by Screening of Medicago truncatula Germplasm Display Contrasting Responses to Cadmium Stress - García de la Torre, Vanesa S.; Coba de la Peña, Teodoro; Pueyo, José J.; Lucas, M. Mercedes (Frontiers in Plant Science, 2021)
Cadmium (Cd) pollution in soils is an increasing problem worldwide, and it affects crop production and safety. We identified Cd-tolerant and -sensitive cultivars by testing 258 accessions of Medicago truncatula at seedling stage, using the relative root growth (RRG) as an indicator of Cd tolerance. The factorial analysis (principal component analysis method) of the different growth parameters analyzed revealed a clear differentiation between accessions depending on the trait (tolerant or sensitive). We obtained a normalized index of Cd tolerance, which further supported the suitability of RRG to assess Cd tolerance at seedling stage. Cd and elements contents were analyzed, but no correlations with the tolerance trait were found. The responses to Cd stress of two accessions which had similar growth in the absence of Cd, different sensitivity to the metal but similar Cd accumulation capacity, were analyzed during germination, seedling stage, and in mature plants. The results showed that the Cd-tolerant accession (CdT) displayed a higher tolerance than the sensitive cultivar (CdS) in all the studied stages. The increased gene expression of the three main NADPH recycling enzymes in CdT might be key for this tolerance. In CdS, Cd stress produced strong expression of most of the genes that encode enzymes involved in glutathione and phytochelatin biosynthesis (MtCYS, MtγECS, and MtGSHS), as well as GR, but it was not enough to avoid a redox status imbalance and oxidative damages. Our results on gene expression, enzyme activity, antioxidant content, and lipid peroxidation indicate different strategies to cope with Cd stress between CdS and CdT, and provide new insights on Cd tolerance and Cd toxicity mechanisms in M. truncatula.